2018
DOI: 10.1002/mar.21097
|View full text |Cite
|
Sign up to set email alerts
|

Impact of relational benefits on trust in the Asian context: Alternative model testing with satisfaction as a mediator and relationship age as a moderator

Abstract: Although it is an established phenomenon in the literature that relational benefits have many positive outcomes, the comparative effect of each type of benefit on different types of trust when customer satisfaction is the mediator, in particular in the Asian context, remains unexplored in the services literature. Therefore, this study, using several alternative models, aims to identify the impacts of confidence benefit, social benefit, and specific treatment benefit on competence, contractual, and goodwill tru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 68 publications
(96 reference statements)
4
19
0
Order By: Relevance
“…Internet service providers need to keep on investing in monitoring and measuring the current customer's satisfaction and expectations. They should carry out various measures to provide confidence benefits to their customers, like Fatima, Mascio, and Johns (2018) found that it could lead to a higher level of competence trust from customers. Fourth, management should reward loyal customers by offering them special treatment, such as price breaks, tailored deals for their needs, and better and more customised services.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Internet service providers need to keep on investing in monitoring and measuring the current customer's satisfaction and expectations. They should carry out various measures to provide confidence benefits to their customers, like Fatima, Mascio, and Johns (2018) found that it could lead to a higher level of competence trust from customers. Fourth, management should reward loyal customers by offering them special treatment, such as price breaks, tailored deals for their needs, and better and more customised services.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Fatima, Mascio, and Johns () examine the role of customer satisfaction in the relationship marketing context in Bangladesh. Specifically, they investigate the impacts of three types of relationship benefits (i.e., confidence benefit, social benefit, and specific treatment benefit) on three types of trust (i.e., competence, contractual, and goodwill trust), along with the mediation roles of customer satisfaction between relationship benefits and trust.…”
Section: Overview Of Studiesmentioning
confidence: 99%
“…For the latter, trust played a certain intermediary or mediation role when scholars discussed the relationship among satisfaction of service quality [ 39 ], organizational culture and leadership performance [ 40 ], and manufacturer–supplier [ 41 ]. Accordingly, some scholars also used satisfaction as an intermediary variable to discuss the influence between trust with green perceived quality, green perceived risk [ 42 ], and relationship benefits [ 43 ].…”
Section: Theoretical Foundationmentioning
confidence: 99%